Cuba : a journey - Timerman, Jacobo; Talbot, Toby (Alfred A. Knopf New York, 1990)
Describes his journey through Cuba using interviews with ordinary Cubans.
Translation of: Cuba hoy, y después.
Keywords: Timerman, Jacobo -- 1923-1999 -- Cuba; Human rights -- 20th century -- Cuba; Politics and government -- 1959-1990 -- Cuba; Social conditions -- 1959-1990 -- Cuba